Burden of falls in China, 1992–2021 and projections to 2030: a systematic analysis for the global burden of disease study 2021 - Sui, Liang; Lv, Yueming; Feng, Kai Xin; Jing, Fu Jie (Frontiers in Public Health, 2025)
BackgroundThe escalating burden of falls in China necessitates a detailed examination to elucidate its dynamics and trends. Using data from the Global Burden of Disease Study (GBD) 2021, this research assessed the burden of falls in China.MethodsData from GBD 2021 were analyzed using Joinpoint regression to identify long-term trends. The impact of mortality and disability-adjusted life years (DALYs) rate for falls was investigated through the age-period-cohort model. Additionally, a decomposition analysis was performed to ascertain the distinct impacts of population growth, aging, and epidemiological changes on the burden of falls from 1992 to 2021. Furthermore, this study employed both the BAPC and Nordpred models to project future burdens of falls.ResultsFrom 1992 to 2021 in China, the age-standardized rates of falls showed divergent trends. Prevalence and incidence rates increased, while mortality rates generally decreased. Males consistently exhibited higher rates than females. The rates of prevalence, incidence, and mortality exhibit a sharp increase beyond the age of 75 in 2021. Decomposition analysis identified aging as the primary driver of increased prevalence and mortality, particularly in females. Joinpoint regression analysis revealed fluctuating trends in prevalence and incidence with periods of increase and decline, and a general decrease in mortality except during brief intervals. DALYs and years of life lost (YLLs) rates generally decreased, with intervals of stabilization and minor increases, while years lived with disability (YLDs) showed significant fluctuations. By 2030, the projected DALYs rate for falls is expected to rise to approximately 547.4 per 100,000. Fractures of the lower extremity predominated as the leading cause of disability post-fall, with hip fractures increasingly contributing to disability among the older adult. Additionally, from 1992 to 2021, the population attributable fraction (PAF) of low bone mineral density for DALYs due to falls increased to 23.2%, with the PAF reaching 33.3% among women in 2021.ConclusionFalls continue to significantly burden public health in China. Our findings highlight the urgent need to develop targeted prevention and intervention strategies that cater to the country’s unique demographic characteristics, aiming to mitigate the growing public health impact of falls.